University Student’s Experiences with Online Synchronous Learning during Covid-19 - Rasto Rasto; Sambas Ali Muhidin; Tutik Inayati; Marsofiyati Marsofiyati (Faculty of Economics, State University of Jakarta., 2021)
This study delivers new insights on students' experiences who have studied their courses at least one semester during the Covid-19 Pandemic. We collected 199 respondents and analyzed the result of the questionnaire. The first finding is that students rather use discussions as a method to conduct online learning in classes. Students also would prefer both methods (asynchronous and synchronous) during online learning. We categorized students' learning experiences into intimacy and connection, supports, coordination and collaboration, technical difficulties, and traits. This study concludes that whole experiences about online synchronous learning did not change, except for the lack of personal support from lecturers when students face difficulties in certain subjects and hardware malfunction during classes. We recommend that lecturers pay more attention to students with less comprehension ability. We also recommend that lecturers run more creative ways other than lecturing in classes and limit lecturing time to decrease boredom.